HIGHWAY HORROR - A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2015)
body 1. Occurrence of decapitation in road traffic accidents is seen in very rarest of rare cases and the injuries sustained also are of vivid nature. Usually cases of road traffic accidents are very common and the investigation of the same are quiet similar in most of the cases. Very rarely cases like decapitation may occur and such cases sometimes also mislead the investigation and create a confusion in concluding the case as an accident or a homicide. In the present case, an adult male, aged 22 years, who was a student, met with an accident on the national highway when he was returning from a dhabha ( small eatery on a road side ) after having his dinner. He was riding a two-wheeler, a motor-bike. The accident was very gruesome and resulted in decapitation of his head. This mislead the investigation and a case of homicide was registered under sections IPC 201 and 302. Later after thorough investigation, visit to the scene of crime and autopsy findings, it was concluded that this was a case of the rarest type of road traffic accident.
Keywords: Decapitation; homicide; road traffic accident